Vocational Students' Ways of Handling the Academic/Vocational Divide - Lisa Ferm (European Research Network Vocational Education and Training (VETNET), 2021)
Purpose: The focus of this article is on Swedish vocational students' own thoughts about different types of knowledge and how these thoughts relate to the forming of their vocational identities. The article reports on a study which investigates how vocational students handle the division between theoretical and practical knowledge as they learn to become skilled industrial workers. Theoretical and practical knowledge are often presented as dichotomies in a hierarchy, where theoretical knowledge is more highly valued than practical knowledge. The division between theoretical and practical knowledge is known in research as "the academic/vocational divide". This divide is particularly relevant to vocational students, as they need to deal with both types of knowledge as they navigate between the contexts of school and work. Methods: This study is part of a research project on vocational students' learning and identity formation. The empirical material is based on qualitative interviews with 44 students enrolled on the industrial programme at Swedish upper secondary schools. Findings: The study revealed three different ways in which vocational students handled the academic/vocational divide: Placing higher value on practical knowledge than on theoretical knowledge, reinforcing the separation between school and work, and selecting theoretical subjects as useful tools for the future.  Conclusions: Two conclusions drawn from the study are that students are aware of the status differences and divisions between practical and theoretical knowledge, and that they handle the academic/vocational divide in an active manner. Students make choices that will help them form a vocational identity or that will give them opportunities for further education and alternative careers. This article challenges and contradicts the image of vocational students as unmotivated and unintellectual, instead portraying them as knowledgeable actors who make strategic choices for their future and are active in forming vocational identities within vocations that require deep and advanced knowledge.